Comparative evaluation of the diagnostic potential of recombinant envelope proteins and native cell culture purified viral antigens of Chikungunya virus. Issue 7 (16th September 2013) - Khan, Mohsin; Dhanwani, Rekha; Kumar, Jyoti S.; Rao, P.V. Lakshmana; Parida, Manmohan
<x xml:space="preserve">Abstract</x> Despite the fact that Chikungunya resurgence is associated with epidemic of unprecedented magnitude, there are challenges in the field of its clinical diagnosis. However, serological tests in an ELISA format provide a rapid tool for the diagnosis of Chikungunya infection. Indeed, ELISAs based on recombinant proteins hold a great promise as these methods are cost effective and are free from the risk of handling biohazardous material. In this study, the performance of recombinant CHIKV antigens was compared in various ELISA formats for the diagnosis of Chikungunya. Two recombinant antigens derived from the envelope proteins of Chikungunya virus were prepared and evaluated by comparing their competence for detecting circulating antibodies in serum samples of patients infected with CHIKV using MAC‐ELISA and indirect IgM‐ELISA. The efficacy of the recombinant antigens was also compared with the native antigen. The indirect antibody capture IgM microplate ELISA revealed ≥90% concordance with the native antigen in detecting the CHIKV specific IgM antibodies whereas the recombinant antigen based MAC‐ELISA showed 100% specificity. The recombinant antigens used in this study were effective and reliable targets for the diagnosis of CHIKV infection and also provide an alternative for native antigen use which is potentially biohazardous. J. Med. Virol. 86:1169–1175, 2014. © 2013 Wiley Periodicals, Inc.